THE ECONOMICS OF EXOGAMOUS MARRIAGE IN SMALL‐SCALE SOCIETIES. (23rd February 2016) - Dow, Gregory K.; Reed, Clyde G.; Woodcock, Simon
Abstract : Marriage is a core institution in almost every human society, including small‐scale societies based on foraging or subsistence agriculture. A crucial dimension of the marriage systems in such societies involves endogamy and exogamy, that is, the choice of a marriage partner from within one's own community or from an outside community. We develop a model in which the exogamy rate is higher when good local matches are scarce due to small community sizes, and when productivity differs across communities due to environmental shocks. These theoretical predictions are supported by econometric analysis of data from the standard cross‐cultural sample. ( JEL D13, J11, N30, Z13)